The antibacterial activity of a novel highly thermostable endolysin, LysKP213, against Gram-negative pathogens is enhanced when combined with outer membrane permeabilizing agents - Chu, Dingjian; Lan, Jing; Liang, Lu; Xia, Kaide; Li, Linlin; Yang, Lan; Liu, Hongmei; Zhang, Tingting (Frontiers in Microbiology, 2024)
Phages and phage-encoded lytic enzymes are promising antimicrobial agents. In this study, we report the isolation and identification of bacteriophage KP2025 from Klebsiella pneumoniae. Bioinformatics analysis of KP2025 revealed a putative endolysin, LysKP213, containing a T4-like_lys domain. Purified LysKP213 was found to be highly thermostable, retaining approximately 44.4% of its lytic activity after 20 h of incubation at 95℃, and approximately 57.5% residual activity after 30 min at 121°C. Furthermore, when administered in combination with polymyxin B or fused at the N-terminus with the antimicrobial peptide cecropin A (CecA), LysKP213 exhibited increased antibacterial activity against Gram-negative pathogens, including K. pneumoniae, Pseudomonas aeruginosa, Acinetobacter baumannii, and Escherichia coli, both in vitro and in vivo. These results indicated that LysKP213 is a highly thermostable endolysin that, when combined with or fused with an outer membrane permeabilizer, has enhanced antibacterial activity and is a candidate agent for the control of infections by Gram-negative pathogens.